ISLAM DAN DEMOKRASI DI TUNISIA : (Kajian Sejarah dan Politik) - Miftahul Khoiri; Nur Anwar (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2022)
Tunisia is a country in the Middle East. Even though they are in the Middle East region which is included in the Arab region, they remain democratic. It all started with the enactment of the jasmine revolution from 2010-2011 which drew the world's attention. Starting from Tunisia, the spirit of revolution which became known as the Arab Spring swept across other Middle Eastern countries. The research study that the author wrote is related to Islam and democracy in Tunisia, to provide an overview of one of the countries in the Arab world which has revolutionized the governance order to become more flexible. In this research study, the historical method was used, which consisted of four stages, namely, finding sources, criticizing, interpreting, and writing. The results of this research study can be said that, Islam and democracy in Tunisia are well developed. This is marked by the existence of a national dialogue when there is a dispute or conflict between groups. When the jasmine revolution occurred in Tunisia which shocked the world, no one would have thought that Tunisia would rise quickly. After carrying out the process of government transition, Tunisia has sped up leaving other Middle Eastern countries in matters of democracy. Tunisia is now the only post-Arab Spring Middle Eastern country that has been able to rise up and implement democratic principles in its country. After the revolution, democratic values ​​were so visible, such as the existence of elections, freedom of opinion, giving space to women, freedom of religion, expression, the emergence of majlis ta'lim Islamic religious studies, the birth of mass organizations is proof that Islam and democracy in Tunisia complement each other.